Problemas de localização e roteamento aplicados na otimização da coleta de resíduos sólidos urbanos no município de Passo Fundo-RS - Barão, Fábio Roberto (2008)
Disposal of municipal solid waste is a problem commonly confronting all industrialized countries around the world. The establishment of selective collection programs, that can be seen as the separation of waste into different fractions as organic (such as food scrapings) and inorganic(such as paper/cardboard, plastic, metal and glass) at source, i.e. in the home or office prior to collection, aiming the reutilization (recycling) of such materials has been seen as one of the most commonly used tools as part of programs seeking the proper management of urban waste, nonetheless, such efforts are based mostly on the motivation of householders in order to achieve suitable performance levels. Focusing on the improvement of such efforts, the current study applies the p-mean facility location problem along with the traveling salesman problem in order to determine the most effective location for voluntary delivery spots containers in the area of downtown Passo Fundo, a city located on the northeast area of the southern State of Rio Grande do Sul in Brazil, as well as aiming on the determination of the most cost effective route for the collection of such material and its destination at the city s landfill The location and routing algorithms were implemented on Lingo 10.0 software. The final result shows a model that can be easily reproduced and that can be repeated whenever necessary, both for the insertion of new collection points as well as the application of such study in different urban areas